Extraction of carotene from moringa oleifera leaves for cosmetics uses - Aziz Zaid, Aziz Qannaf (2016)
In this research, carotene in the Moringa Oeifera leaves will be extracted by using Soxhlet extraction method. Carotene as pigment that naturally contained in most vegetables is important source of nutrients used for pharmaceutical and cosmetic. The main constituent of the carotene which is beta-carotene will be investigated. Two variables were chosen to investigate the effect of different solvent on the extraction and beta-carotene concentration. Samples with different solvent will be prepared which the solvents are acetone, petroleum ether and water respectively. After the extraction process, the mixture of carotene and solvent will be separated using rotary evaporator in order to get the extracted carotene. Then, the extracted carotene was analysed using HPLC to determine the beta-carotene concentration.The best type of solvent use to extract the beta carotene from Moringa Oleifera is petroleum ether and was proven from the HPLC analysis based on the area of peak.